Internalization of Islamic Leadership Character Values in State Islamic Senior High School Students (MAN) through Madrasah Intra-Student Organizations - Ichwanudin; Susanto, Happy; Syam, Aldo Redho (Journal of Islamic Education, 2025)
This study aims to explore the internalization of Islamic leadership character values and to find out the challenges, solutions and results of internalizing Islamic leadership character values. The method used is a qualitative approach with descriptive analysis ethnographic design, which involves semi-structured interviews, participatory observation, and documentation. The subjects of the research were the mentor teacher, and students. Data analysis followed three stages, namely: data reduction, data presentation, and conclusion drawing or verification. The results showed that Madrasah Intra Student Organization (OSIM: Organisasi Siswa Intra Madrasah) activities play an important role in shaping student leadership character, with a focus on developing religiosity, moderation, honesty, trustworthy cooperation, and social care. Students who are actively involved in the OSIM experience improvements in communication skills, decision-making, and self-confidence. In addition, students also show better behaviour in social and academic interactions and are able to apply Islamic values in daily life. The conclusion of this study confirms that the internalization of Islamic leadership character values through the OSIM is effective in forming a young generation with integrity and noble character. Therefore, it is recommended that educational institutions continue to integrate Islamic values into the curriculum and extracurricular activities and provide greater support to coaches in implementing effective internalization strategies. Thus, it is hoped that the younger generation will not only excel in academic aspects but also have a strong commitment to Islamic values so that they are able to face future challenges with high integrity and social responsibility.